The impact of mindfulness meditation on social and moral behavior: Does mindfulness enhance other-oriented motivation or decrease monetary reward salience? - Feruglio, Susanna; Panasiti, Maria Serena; Crescentini, Cristiano; Aglioti, Salvatore Maria; Ponsi, Giorgia (Frontiers in Integrative Neuroscience, 2022)
This perspective article provides an overview of the impact of mindfulness meditation (MM) on social and moral behavior. In mindfulness research, prosocial behavior has been operationalized as helping behavior, altruistic redistribution of funds, reparative behavior, or monetary donation. Studies concerning moral behavior are still scarce. Despite inconsistent evidence, several studies found a beneficial effect of mindfulness on prosocial outcomes (i.e., a higher propensity to spend or give away money for the sake of other individuals). However, since the employed tasks were reward-based, participants’ decisions also directly affected their own payoff by reducing it. Crucially, MM also affects self-control circuitry and reduces reward-seeking behaviors and reward salience by making rewards less tempting. We have discussed evidence suggesting how challenging it may be to dissociate the specific weight of enhanced other-oriented motivation from one of the decreased monetary reward salience in explaining meditators’ behavior. Future higher-quality studies are needed to address this open issue.